Present situation and future potential of cassava in Indonesia - Saleh, Nasir; Hartojo, K.; Suyamto (International Center for Tropical Agriculture, 2001)
Cassava (Manihot esculenta Crantz.) in Indonesia can be considered as a controversial crop. This crop has a tremendous yield potential of almost 100 t of fresh roots/ha, but official data show that its actual productivity is only 10-20% of its biological potential. It is considered to have multiple end uses, such as food, feed, raw material for industry and export. Very often, however, cassava farmers complain about the low and unstable price they receive for their product. A longer list can be developed concerning the contradictory nature of cassava. This in turn should be perceived as a special challenge to those who are more concerned about the improvement of people's living standards rather than the crop itself. Starting from 1973, the cassava production system in Indonesia has shown a declining annual growth rate for the harvested area (-0.41%), but an increasing rate for both production (1.53%) and yield (1.93%). Since the standard deviation of the rate is much greater than its average, values of the rate and its sign (positive and negative) should be considered as a trend indicator only, and they can not be used for prediction purposes. At present, cassava in Indonesia is harvested from around 1.2 million ha, producing around 15-17 million tonnes of fresh roots, as the yield is only about 12-13 t/ha. Most cassava is produced by small farmers that are weak in resources endowment, either in economic or social terms. Little purchased inputs, especially chemical or inorganic fertilizers, are applied, and as a result cassava production is frequently blamed as the cause of soil degradation. The crop is mostly grown in upland areas with undulating topography. Since its planting time should be compatible with the distribution of rainfall, the flexibility in planting and harvesting time is limited. As a consequence, the existence of a peak in planting and harvesting time is difficult to avoid. Abundance of cassava roots during the peak harvesting time results in low prices. From an individual farmer’s point of view, his income is determined by his productivity level. Logically, any improvement in productivity should increase farmer's income. However, this rarely happens, because the price is governed by the total amount of roots produced. As price fluctuation is the result of supply and demand imbalance, any decrease in price can be perceived as an indicator of limited demand. There is a belief that cassava farmers, especially the low-income groups, are trapped in a vicious cycle: changes in yield-planted area-production, are countered by changes in prices which go up and down. This condition in turn prevents farmers from improving their income. If the opinion that demand is the most important limiting factor for production growth is true, the best solution should be a demand-led strategy. Demand for cassava in Indonesia is mainly in the areas of food, industry (mainly processing of starch and starch-based products), export and feed. Future prospects for using cassava as food will depend mainly on: (1) rice availability, since rice is the most preferred staple food for Indonesian people; and (2) cassava product development activities, as the social bias against cassava as being a food for the poor is strong and real. The existence of starch processing and starch-based industries, especially on a large scale, have been present for some time, but their role in improving farmers' welfare should be questioned. The growth in cassava exports will face two barriers: first, strong competition from Thailand, and secondly, the domestic price. Demand for cassava as a raw material for production of feed will depend on its price in relation to that of maize.